Notas sobre ecología y distribución del género Lepanthes (Orchidaceae) en Cuba, con una lista actualizada y revisada - Llamacho Olmo, Juan A. (2016)
Notes about ecology and distribution of the genus Lepanthes in Cuba are given. The paper includes a list of all the species recorded for the island, and the location of their types in herbaria.